2019
DOI: 10.1002/cmdc.201900203
|View full text |Cite
|
Sign up to set email alerts
|

Development of Tetrahydroindazole‐Based Potent and Selective Sigma‐2 Receptor Ligands

Abstract: The sigma‐2 receptor has been shown to play important roles in a number of important diseases, including central nervous system (CNS) disorders and cancer. However, mechanisms by which sigma‐2 contributes to these diseases remain unclear. The development of new sigma‐2 ligands that can be used to probe the function of this protein and potentially as drug discovery leads is therefore of great importance. Herein we report the development of a series of tetrahydroindazole compounds that are highly potent and sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…Compounds NUCC-54129, NUCC-200823, NUCC-176289 and other NUCC analogs were synthesized according to methods described in US Patent 10,435,375 and in ( Iyamu et al, 2019a , 2019b ). NUCC analogs were dissolved in 20% DMSO and 80% water.…”
Section: Methodsmentioning
confidence: 99%
“…Compounds NUCC-54129, NUCC-200823, NUCC-176289 and other NUCC analogs were synthesized according to methods described in US Patent 10,435,375 and in ( Iyamu et al, 2019a , 2019b ). NUCC analogs were dissolved in 20% DMSO and 80% water.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, the most recent σ 2 R ligands pharmacophore was published in 2019 by scientists from Northwestern University. 86 They developed a series of tetrahydroindazoles and used the obtained SAR data to build the model using the PHASE module as implemented in the Schrödinger software suite. This pharmacophore model consists of one PI group, one HYAr ring, and three HY moieties ( Figure 6 B).…”
Section: Pharmacophore Models For σR Ligandsmentioning
confidence: 99%
“…This ESTEVE pharmacophore outperformed previously published models and, according to the authors, showed better results than molecular docking. On the other hand, the most recent σ 2 R ligands pharmacophore was published in 2019 by scientists from Northwestern University . They developed a series of tetrahydroindazoles and used the obtained SAR data to build the model using the PHASE module as implemented in the Schrödinger software suite.…”
Section: Pharmacophore Models For σR Ligandsmentioning
confidence: 99%